Trigo BRS 394 irrigado no Cerrado Mato-Grossense : interações nitrogênio-potássio e nitrogênio-enxofre - Santos, Carolina Silva Alves dos (2022)
Considering the importance that nutrients such as Nitrogen, Potassium and Sulfur play in the physiological development of cultivated plants, in order to answer what would be the best nutritional combinations to be adopted in the cultivation of wheat in a Cerrado environment, the objective was to evaluate nitrogen-potassium and nitrogen-sulfur interactions plant development, yield and grain quality of wheat cv. BRS 394 irrigated. The experiment was carried out in the field, in soil classified as dystrophic Red Latosol. The cultivar BRS 394 was used in the 2018 and 2019 harvests. The treatments corresponded to five doses of nitrogen (0, 70, 140, 210 and 280 kg ha-1 ), five doses of potassium (0, 50, 100, 150 and 200 kg ha-1 ) and five sulfur doses (0, 25, 50, 75 and 100 kg ha-1 ), totaling 13 combinations between nutrients in each of the experiments (NxK and NxS). The treatments were randomized in blocks, with four replications. The experimental plots consisted of 9 lines, 6.0 m long and 0.20 m between lines, with a density of 350 viable seeds per m2 and a useful area of 4.5 m2 . The chemical and physical characterization of the soil was carried out in the two years of cultivation in the 0-20 cm layer. The following groups of response variables were evaluated: nutritional, productive and qualitative characteristics in both seasons. Data were subjected to analysis of variance and means analyzed by polynomial regression at 5% and 10% by the F test. The combination of doses of nitrogen (154.05 kg ha-1 ) and potassium (134.78 kg ha-1 ) provided maximum grain yield of 3043 kg ha-1 in the 2018 crop. For SPAD reading in the 2019 crop there was quadratic fit to the response surface model. The nitrogen concentration in the grains, in the 2018 crop, in the nitrogen and potassium levels, was adjusted to the linear response surface model. The use of the respective doses, 150 and 130 kg ha-1 of nitrogen and potassium provided productive and nutritional increments that improved the industrial quality, as well as increased the efficiency in the use of water in most of the variables analyzed in the present study. The combination of doses of N (216 kg ha-1 ) and S (63 kg ha-1 ) provided a yield of 3888 kg ha-1 in the 2018 crop, with the other productive characteristics evaluated following the same trend in that crop. There was better productive performance in 2018 at doses of 200 and 90 kg ha-1 of N and S, respectively. In the 2019 harvest, no significant results were observed (p>0.10).